Two Duplicated Ptpn6 Homeologs Cooperatively and Negatively Regulate RLR-Mediated IFN Response in Hexaploid Gibel Carp - Tong, Jin-Feng; Zhou, Li; Li, Shun; Lu, Long-Feng; Li, Zhuo-Cong; Li, Zhi; Gan, Rui-Hai; Mou, Cheng-Yan; Zhang, Qi-Ya; Wang, Zhong-Wei; Zhang, Xiao-Juan; Wang, Yang; et al. (Frontiers in Immunology, 2021)
Src homology region 2 domain-containing phosphatase 1 (SHP1), encoded by the protein tyrosine phosphatase nonreceptor type 6 (ptpn6) gene, belongs to the family of protein tyrosine phosphatases (PTPs) and participates in multiple signaling pathways of immune cells. However, the mechanism of SHP1 in regulating fish immunity is largely unknown. In this study, we first identified two gibel carp (Carassius gibelio) ptpn6 homeologs (Cgptpn6-A and Cgptpn6-B), each of which had three alleles with high identities. Then, relative to Cgptpn6-B, dominant expression in adult tissues and higher upregulated expression of Cgptpn6-A induced by polyinosinic-polycytidylic acid (poly I:C), poly deoxyadenylic-deoxythymidylic (dA:dT) acid and spring viremia of carp virus (SVCV) were uncovered. Finally, we demonstrated that CgSHP1-A (encoded by the Cgptpn6-A gene) and CgSHP1-B (encoded by the Cgptpn6-B gene) act as negative regulators of the RIG-I-like receptor (RLR)-mediated interferon (IFN) response via two mechanisms: the inhibition of CaTBK1-induced phosphorylation of CaMITA shared by CgSHP1-A and CgSHP1-B, and the autophagic degradation of CaMITA exclusively by CgSHP1-A. Meanwhile, the data support that CgSHP1-A and CgSHP1-B have sub-functionalized and that CgSHP1-A overwhelmingly dominates CgSHP1-B in the process of RLR-mediated IFN response. The current study not only sheds light on the regulative mechanism of SHP1 in fish immunity, but also provides a typical case of duplicated gene evolutionary fates.